Humans with Atherosclerosis have Impaired ABCA1 Cholesterol Efflux and Enhanced HDL Oxidation by Myeloperoxidase - Shao, Baohai (2014)
RATIONALE: The efflux capacity of HDL with cultured macrophages associates strongly and negatively with CAD status, indicating that impaired sterol efflux capacity might be a marker—and perhaps mediator—of atherosclerotic burden. However, the mechanisms that contribute to impaired sterol efflux capacity remain poorly understood. OBJECTIVE: To determine the relationship between myeloperoxidase-mediated oxidative damage to apoA-I, the major HDL protein, and the ability of HDL to remove cellular cholesterol by the ABCA1 pathway. METHODS AND RESULTS: We quantified both site-specific oxidation of apoA-I and HDL’s ABCA1 cholesterol efflux capacity in control subjects and subjects with stable coronary artery disease or acute coronary syndrome. The CAD and ACS subjects had higher levels of chlorinated tyrosine-192 and oxidized methionine-148 than the control subjects. In contrast, plasma levels of MPO did not differ between the groups. HDL from the CAD and ACS subjects was less able to accept cholesterol from cells expressing ABCA1 than HDL from control subjects. Levels of chlorinated tyrosine and oxidized methionine associated inversely with ABCA1 efflux capacity and positively with atherosclerotic disease status. These differences remained significant after adjusting for HDL-cholesterol levels. CONCLUSIONS: Our observations indicate that MPO may contribute to the generation of dysfunctional HDL with impaired ABCA1 efflux capacity in humans with atherosclerosis. Quantification of chlorotyrosine and oxidized methionine in circulating HDL might be useful indicators of the risk of cardiovascular disease that are independent of HDL-cholesterol.